2011
DOI: 10.2500/aap.2011.32.3482
|View full text |Cite
|
Sign up to set email alerts
|

Onset and duration of attenuation of exercise-induced bronchoconstriction in children by single-dose of montelukast

Abstract: Single-dose montelukast attenuates exercise-induced bronchoconstriction (EIB) in adults within 2 hours postdose and lasting through 24 hours. This study evaluated the onset and duration of EIB attenuation in children after a single dose of montelukast. A randomized, double-blind, placebo-controlled, two-period crossover study was performed. Patients (n = 66) aged 4-14 years, with preexercise forced expiratory volume in 1 second of (FEV(1)) ≥70% predicted and maximum percentage fall in FEV(1) of ≥20% at two scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The efficacy of montelukast for preventing a maximum decrease in forced expiratory volume in 1 second (FEV1) after exercise is significantly higher than that of FP, and the high leukotriene E4/fractional exhaled nitric oxide ratio is associated with a greater response to montelukast than to FP for EIB therapy 70. Another randomized, double-blind, placebo-controlled, two-period crossover study evaluated the onset and duration of EIB attenuation in children after a single dose of montelukast and found single-dose montelukast provided rapid and sustained EIB attenuation in children 71. Effect of montelukast was also shown to be better than salmeterol added to inhaled fluticasone on EIB in children in a randomized, double-blind, double-dummy, multicenter, two-period, 4-week, crossover study 72.…”
Section: Effectiveness Clinical Efficacy and Safety Of Montelukast mentioning
confidence: 99%
“…The efficacy of montelukast for preventing a maximum decrease in forced expiratory volume in 1 second (FEV1) after exercise is significantly higher than that of FP, and the high leukotriene E4/fractional exhaled nitric oxide ratio is associated with a greater response to montelukast than to FP for EIB therapy 70. Another randomized, double-blind, placebo-controlled, two-period crossover study evaluated the onset and duration of EIB attenuation in children after a single dose of montelukast and found single-dose montelukast provided rapid and sustained EIB attenuation in children 71. Effect of montelukast was also shown to be better than salmeterol added to inhaled fluticasone on EIB in children in a randomized, double-blind, double-dummy, multicenter, two-period, 4-week, crossover study 72.…”
Section: Effectiveness Clinical Efficacy and Safety Of Montelukast mentioning
confidence: 99%
“…Effective treatment showed an increased AUC over a given time period when compared to a control. One study [3] measured the AUC for the first 60 min postexercise and found montelukast to be significantly more effective at attenuating EIB than placebo [3]. The results for AUC obtained by Stelmachet al demonstrate that coadministration of budesonide with montelukast, and montelukast monotherapy were significantly more efficacious than treatment with budesonide alone or budesonide with formoterol.…”
Section: Titlementioning
confidence: 65%
“…The therapeutic benefits were sustained for up to 8 h post-treatment. Wasfi et al evaluated the onset and duration of therapeutic effect, following a single dose of montelukast in a crossover study [3]. This study measured maximum percentage fall in FEV1 after EC, 2 and 24 h post-treatment.…”
Section: Titlementioning
confidence: 99%
See 2 more Smart Citations